Tracheal regeneration with acellular human amniotic membrane and 15-deoxy-∆12,14prostaglandinj2 nanoparticles in a rabbit model - ANNA FLAVIA R.S. MIGGIOLARO; ALINE L. TAKEJIMA; JULIO CESAR FRANCISCO; LÚCIA DE NORONHA; MILKA L. TAKEJIMA; KATIA FOLTZ; ALOYSIO ENCK; LUANA TANNOUS; ROSSANA B. SIMEONI; PRISCILA E.F. STRICKER; KATHERINE A.T. CARVALHO; LUIZ CESAR GUARITA-SOUZA (Anais da Academia Brasileira de Ciências, 2023)
Abstract The treatment of tracheal pathologies remains challenging.Nanotechnology allows adding substances to decellularized human amniotic membrane (DHAM), such as 15-Deoxy-∆12,14ProstaglandinJ2 nanoparticles (15D-PGJ2-NC).This study performed a tracheotomy in rabbits randomized into three groups.The tissue repair process was evaluated when treated with DHAM associated or not with 15D-PGJ2-NC.The average of the area in the control group was 54.76% smaller than DHAM group and 41.98% smaller than DHAM + 15D-PGJ2-NC group (p=0.004 for both).The DHAM + 15D-PGJ2-NC group had significantly more immature cartilage (p=0.015).DHAM impregnated with 15D-PGJ2-NC could provide support for the healing of the tracheal defect and may prevent reduction of its lumen.